PENGARUH HARGA DAN DESAIN TERHADAP MINAT PEMBELIAN DIfDISTRO OVERTOUN MALANG - Muhammad Syaiful Rojikin; Muhammad Mansur (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
DABSTRACTW               MarketingHmanagementKisAtheAartKandLscienceKofLchoosingKtheLtargetmarketKandPreachingOforOmaintainingPandKgrowingLcustomersPbyPcreating.               This studyHaimsKtoGdetermineKhowKmuchLinfluence the harha and design have on consumers' interest in being Overtoun Distro Malang. The results of this study               indicate that prices and designs can be said to be good. Pricesand designs have an effect of 21% on buying interest Keywords: Price, Design, Purchase Interest